Nutrition and somatic traits of women with different physical activity and various menstrual status - Jan Czeczelewski (Kazimierz Wielki University, 2022)
Background. There are publications which indicate a relationship between dietary pattern and somatic traits. Others report on link between somatic traits and physical activity. However, sparse studies discuss relationship between these three factors, i.e. nutrition, somatic traits and physical activity. Objectives. This survey aimed to analyze relationships between nutrition (amount and source of energy in food) and somatic traits (body height, body mass, fat content of the body) of women with different physical activity and various menstrual status. Material and methods. Investigations covered 312 women who were assessed for: somatic traits, average daily energy consumption and percentage contribution of proteins, fats and carbohydrates in providing energy. The physical activity was assessed by computing the physical activity index (PAI) being a ratio of daily energy expenditure (DEE) to basal metabolic rate (BMR). Among the women two groups were distinguished based on centile charts of the PAI developed for a given population, i.e.: women with a low (PAI≤10 cpts) and women with a high (PAI≥90 cpts) level of physical activity. Results. The highly physically active women were characterized by a lower body fat content, lower BMI values, and higher percentage of lean body mass compared to the women with a low level of physical activity. The highly active women showed a tendency for an increased consumption of whole-meal bread, milk and dairy products, vegetables (including potatoes), fruits, and sweets as well as a tendency for a reduced consumption of meat and processed meat products, both types of butter, and lard, compared to the little active women. Conclusions. It seems that the physical activity of the women had a direct impact on their nutrition. In turn, by affecting the somatic traits (body mass and composition), their eating habits could influence their physical activity.